Increased nerve growth factor serum levels in top athletes - Bonini, M.; Fioretti, D.; Sargentini, V.; Giacco, S. del; Rinaldi, M.; Tranquilli, C.; Bonini, S. (Clinical Journal of Sport Medicine, 2013)
Objective: The nerve growth factor (NGF) is the main neurotrophin, which, besides being an important growth factor for nerves, plays an important role as a mediator of inflammation. Nerve growth factor has been shown to increase in relation to stress stimuli and in allergic diseases in humans as well as after physical exercise in animal models. This study aims at evaluating NGF serum levels in top athletes, a population sample in which allergic and neuro-immune diseases are reported with a significantly increased prevalence.